Peran Majelis Pengawas Wilayah Notaris dan Majelis Kehormatan Notaris Terhadap Pembinaan dan Pngawasan Notaris - Purwantoro Purwantoro; Fatriansyah Fatriansyah (Recital Review, 2019)
Notary supervision distinguish between the behavior and the actions undertaken by the Notary in running the office by the Regional Supervisor Notary while the behavior and actions undertaken by the Notary office outside run supervised by Notary Honorary Council. The supervision is basically a form of legal protection against the Notary itself because of the presence of an oversight, then every Notary in behavior and actions both in the running of his office and outside always within the law. Supervision conducted by the Supervisory Council of the Notary region should still be there because it is very instrumental in the development and monitoring of the performance of its members in order to minimize errors and violations in carrying out his duties.